Sensitivity of zebrafish (Danio rerio) embryos to hospital effluent compared to Daphnia magna and Aliivibrio fischeri - Wittlerová, Martina; Jírová, Gabriela; Vlková, Alena; Kejlová, Kristina; Malý, Marek; Heinonen, T; Wittlingerová, Zdeňka; Zimová, Magdalena (Physiological research, 2020)
The Fish Embryo Acute Toxicity (FET) Test was adopted by the Organisation for Economic Co-operation and Development as OECD TG 236 in 2013. The test has been designed to determine acute toxicity of chemicals on embryonic stages of fish and proposed as an alternative method to the Fish Acute Toxicity Test performed according to OECD TG 203. In recent years fish embryos were used not only in the assessment of toxicity of chemicals but also for environmental and wastewater samples. In our study we investigated the acute toxicity of treated wastewater from seven hospitals in the Czech Republic. Our main purpose was to compare the suitability and sensitivity of zebrafish embryos with the sensitivity of two other aquatic organisms commonly used for wastewater testing - Daphnia magna and Aliivibrio fischeri. For the aim of this study, in addition to the lethal endpoints of the FET test, sublethal effects such as delayed heartbeat, lack of blood circulation, pericardial and yolk sac edema, spinal curvature and pigmentation failures were evaluated. The comparison of three species demonstrated that the sensitivity of zebrafish embryos is comparable or in some cases higher than the sensitivity of D. magna and A. fischeri. The inclusion of sublethal endpoints caused statistically significant increase of the FET test efficiency in the range of 1-12 %. Based on our results, the FET test, especially with the addition of sublethal effects evaluation, can be considered as a sufficiently sensitive and useful additional tool for ecotoxicity testing of the acute toxicity potential of hospital effluents.
Keywords: odpadní voda; Environmental Monitoring; nemocnice; Risk Assessment; Water Pollutants, Chemical; zvířata; reprodukovatelnost výsledků; Daphnia; Toxicity Tests, Acute; embryo nesavčí; Time Factors; Zebrafish; testy akutní toxicity; Hospitals; Wastewater; dánio pruhované; Embryo, Nonmammalian; Lethal Dose 50; časové faktory; hodnocení rizik; Animals; LD50; Reproducibility of Results; Aliivibrio fischeri; chemické látky znečišťující vodu; monitorování životního prostředí